ANALISIS PREDIKSI KEBANGKRUTAN BERDASARKAN METODE ALTMAN Z-SCORE (STUDI KASUS PADA BANK BUMN YANG TERDAFTAR DI BEI) - Korry, I Komang Try Satriawan; Dewi, Made Pratiwi; Ningsih, Ni Luh Anik Puspa (Buletin Studi Ekonomi; VOL.24.NO.2.AGUSTUS 2019DO - 10.24843/BSE.2019.v24.i02.p03, 2019)
Abstract: Bankruptcy Prediction Analysis Based on the Altman Z-Score Method (Case Study of State-Owned Banks Registered on the IDX). Bankruptcy phenomena can occur in every company. Based on data from the Deposit Insurance Agency (LPS), there were 90 banks liquidated since 2005 until mid-2018. Based on the phenomenon of bankruptcy that occurred, it was important for banks to be no exception for state-owned banks to recognize the symptoms of financial distress that led to bankruptcy. The purpose of this study was to determine the prediction of bankruptcy based on the Altman Z-Score method on state-owned banks listed on the Indonesia Stock Exchange (IDX). The data analysis technique used in this study is descriptive analysis techniques. The sample in this study used four state-owned banks, namely Bank Negara Indonesia, Bank Rakyat Indonesia, Bank Tabungan Nasional, and Bank Mandiri with the technique of determining saturated sampling samples and the data used were financial statements for the 2014-2017 period obtained through official IDX sites (www.idx.co.id). The results of the study show that all state-owned banks are in the gray area for the period of 2014-2017 because the value of the Z-score obtained is between 1.1 and 2.6.